Studi Temperatur Beton Massa pada Masa Pengerasan (Hardening Time) Menggunakan Suhu Air Dingin dan Kadar Fly Ash - Bagus Nurrohmat; Daffa Rozaan Fayyadh; Sumirin Sumirin (Pusat riset dan Inovasi Nasional, 2026)
Modern infrastructure development often involves the use of mass concrete in large structural elements such as pile caps and foundations. However, massive concrete volumes trigger a significant temperature increase due to the heat of hydration that is difficult to dissipate, posing a risk of thermal stress and structural cracking. This study aims to analyze the temperature rise behavior of mass concrete and evaluate the effectiveness of combining chilled water and fly ash substitution in minimizing these thermal cracking risks.The research method employs a quantitative approach through laboratory testing at PT Adhimix RMC Plant Kaligawe. Specimen blocks measuring 40 x 40 x 100 cm were divided into three variations: normal concrete (BN), concrete with chilled water and 15% fly ash (BAF), and concrete with 25% fly ash (BF). Temperature was monitored using thermocouples at the core and surface for 14 days, then validated using the Portland Cement Association (PCA) formula. The results indicate that the integration of chilled water with 15% fly ash and the use of 25% fly ash significantly controlled extreme temperature surges at the 5th hour. The combination of chilled water and 15% fly ash produced the lowest core temperature of 37.3°C, far below the control concrete which reached 62.4°C. This proves that the combination of precooling methods and fly ash substitution is effective in reducing the heat of hydration during the early hardening period, although the use of 25% fly ash was found to be more stable in maintaining mass concrete temperature.